Characterisation of metabolic acidosis in Kenyan children admitted to hospital for acute non-surgical conditions. - Sasi, P; English, M; Berkley, J; Lowe, B; Shebe, M; Mwakesi, R; Kokwaro, G (2006)
Metabolic acidosis is associated with most severe malaria deaths in African children, and most deaths occur before maximum antimalarial action is achieved. Thus, specific acidosis treatment may reduce mortality. However, the underlying mechanisms remain poorly understood and no specific interventions have been developed. A detailed characterisation of this acidosis is critical in treatment development. We used the traditional and Stewart's approach to characterise acidosis in consecutive paediatric admissions for malaria and other acute non-surgical conditions to Kilifi District Hospital in Kenya. The overall acidosis prevalence was 21%. Gastroenteritis had the highest prevalence (61%). Both the mean albumin-corrected anion gap and the strong ion gap were high (>13 mmol/l and >0 mmol/l, respectively) in malaria, gastroenteritis, lower respiratory tract infection and malnutrition. Presence of salicylate in plasma was not associated with acidosis but was associated with signs of severe illness (odds ratio 2.11, 95% CI 1.1-4.2). In malaria, mean (95% CI) strong ion gap was 15 (14-7) mmol/l, and lactate, creatinine and inorganic phosphorous explained only approximately 40% of the variability in base excess (adjusted R2 = 0.397). Acidosis may be more common than previously recognised amongst paediatric admissions in Africa and is characterised by the presence of currently unidentified strong anions. In malaria, lactate and ketones, but not salicylate, are associated with acidosis. However, unidentified anions may be more important.